KEANEKARAGAMAN SERANGGA HAMA, PREDATOR, DAN PARASITOID PADA PERKEBUNAN KOPI SEAT UNGARAN - Samsuri (Program Studi Agroteknologi INSTIPER, 2019)
The objective of the research were to know the diversty of insect pests with their Predators and Parasitoids on Stiper Eduagrotourisme Coffee Plantation at Ungaran. The research was conducted at October to Desember 2019. Visually searching to absolute measure of population size immobile insect and malaisetrap were aplicated to mobil insect collection. Insect species diversity was analyzed using the Shannon-Wiener Index and the evenness is calculated according to the formula Pielou. The results were obtained 6537 individuals consisting of 7 orders, 18 families and 20 spesies. Diversity index (H ') insect in the coffee garden is 0,7517 and classified in the low category. The ecological role of insects in the coffee garden are pest insects as much as 5 family with 9 species, predator as much as 4 family with 5 species , and parasitoid as much as 4 family with 4 species. Keyword: Pests of coffee, predators, parasitoids, Insect diversity